Gestión estratégica corporativa y su relación en los procesos administrativos de secretaría general de la Facultad de Ciencias Jurídicas Sociales y de la Educación - Galeas Naranjo, Verónica Viviana (2020)
This case study was carried out in support of the following research topic which is corporate strategic management and its relationship in the administrative processes of the general secretary of the Faculty of Social Law and Education Sciences of the Technical University of Babahoyo, in the development of this study, the deductive method was used that allows starting from the general to the specific, that is to say that this method allows obtaining relevant and reliable information and thus being able to obtain knowledge about the subject studied, one of the techniques used in the Data collection was the survey providing data of great importance, through this technique it was possible to know the difficulty that exists in the general secretary at the time of establishing strategic management within her work area, this leads to administrative processes not being fulfilled in an efficient way which causes that the objective is not fulfilled in the desired way or of the institution given that strategic management is important within the organization because it is a process where the strategies to implement them are identified and described and with this have a better performance and competitive advantage in the organization, this research had The objective is to identify the relationship that corporate strategic management has with administrative processes.